The Discovery of Vibrio harveyi on Litopenaeus vannamei Infected White Feces Disease in Situbondo, East Java - Sumini Sumini; Rahayu Kusdarwati (Jurnal Perikanan Universitas Gadjah Mada, 2020)
This research was conducted to discover Vibrio harveyi infected vannamei shrimp with White Feces Disease (WFD) in Situbondo, East Java Province. This research was conducted in November 2017 until September  2018. All Vibrio isolates from shrimp infected WFD were identified with biochemical tests, Analytical Profile Index/ API 20NE (BioMeriuex), and PCR with specific primers for V. harveyi. Additional parameters were the water quality, plankton brackishwater pond abundance, and antibiotic resistance test. Result showed that from 17 bacterial isolates identified, 10 isolates were V. harveyi (58.82%), three isolates were V. alginolyticus (17.65%), one V. fluvialis isolate (5.88%), one V. parahaemolyticus isolate (5.88%), and two non Vibrio isolates which were identified as Shewanella putrefaciens (11.76%). All isolates of V. harveyi also showed resistance activity on more than one antibiotic. Poor water quality had been identified as abnormal result of pH, alkalinity, salinity, ammonia levels and total organic matter level. Plankton abundance observation showed that Chloropyceae, Diatom, and Dinoflagellata dominated all sampled brackishwater ponds. This research concluded that V. harveyi were discovered on vannamei shrimp with poor water quality and plankton abundance in the pond samples.